Teaching and Learning Elementary and Middle School Mathematics - Sheffield, Linda Jensen; Cruikshank, Douglas E. ([kn] : John Wiley and Sons, 2000)
Teaching mathematics to elementary and middle school students; Creating and solving problems; Technology in teaching; Rational numbers and operations; Probability; Geometry; Algebra; Organizing math instruction.
Keywords: Mathematics; Middle school mathematics; Mathematics -- Study and Teaching (Elementary); Mathematics -- Study and teaching (Middle school)